An Empirical Analysis for the Effects of Accounting and Auditing Standards and Corporate Governance on Macroeconomic Stability - Hülya Kesici Çalışkan; Ayşe Atılgan Sarıdoğan (İktisat Politikası Araştırmaları Dergisi)
Macroeconomic stability is important for a country’s sustainable economic growth and social welfare. There are many economic and political factors affecting macroeconomic stability at sectoral, national and international levels. In financial system, while investors lend their savings to companies, they decide according to performance indicators of companies in financial statements. However, accuracy and reliability of information in financial statements of companies depends on level of development in accounting and auditing standards on one hand, and on corporate management capacity on other. There is asymmetrical information about accuracy of financial information of firm between company managers and investors who want to invest in company. This asymmetrical information can cause investors to make wrong choices, triggering financial and economic instability. In this context, developments in accounting and auditing standards and corporate governance level play an important role in solving asymmetric information problem and maintaining macroeconomic stability. In this context, main purpose of this study is to analyse empirically effects of accounting and auditing standards and corporate governance on macroeconomic stability. According to results of study; explanatory variables, Corporate governance and Strength auditing accounting standards affect dependent variable in same direction. The improvement of Accounting and Auditing standards and Corporate Governance climate is important not only for strengthening of firms and sectors, but also for national macroeconomic stability. As a result, giving sufficient importance to development of accounting and auditing standards and corporate governance in economic policy designs will contribute to preservation and strengthening of macroeconomic stability.